Penyusunan Peraturan Desa Tentang Bale Mediasi Melalui Penyuluhan dan Monitoring Pada Desa Rumak, Kecamatan Kediri, Kabupaten Lombok Barat - Rinda Philona; I Made Suradana; Novita Listyaningrum (Jurnal Gema Ngabdi, 2021)
This extension and monitoring activity aims to provide knowledge and understanding to the people of Rumak Village about how the basic mechanisms and knowledge in drafting a village regulation, in this case Bale Mediation, is an institution that carries out mediation, guidance and coordination functions in the implementation of mediation in the community in accordance with local wisdom. This counseling also simultaneously monitors conditions or problems that occur in the Rumak Village community which can be resolved through mediation or non-litigation. This outreach activity was held thanks to the cooperation of various parties, namely: Rumak Village Officials consisting of the government of Village, the Secretary of the Hamlet and Bhabinkamtibmas, the NTB Province Bale Mediation Institute and Law Faculty Lecturers from various existing universities. Extension activities are carried out using the lecture and discussion method. All extension participants followed the series of events well to the end and were very enthusiastic by providing various kinds of questions that often occur. Therefore, it can be concluded that the implementation of this counseling went well and was successful where the material presented could be well absorbed by the Rumak Village officials and they would implement everything to be applied to the Rumak Village community.